Investigation on leakage vortex cavitation and corresponding enstrophy characteristics in a liquid nitrogen inducer. (January 2023) - Chen, Zhandong; Yang, Shidong; Li, Xiaojun; Li, Yongpeng; Li, Linmin
Highlights: The cavitation model is modified to accommodate cryogenic cavitation. The enstrophy dissipation rate is used to analyze the energy loss of TLV. The intensity of TLV is weakened with the increasing temperature. Periodic evolution of two TLV structures, including PTLV and STLV, results in variation of enstrophy. Abstract: A modified thermal cavitation model was employed to study the thermodynamic cavitation and effects of tip leakage vortex (TLV) on hydraulic losses in a three-blade inducer. Comparative analyses for TLV cavitation under different temperatures were presented. The tip leakage flow was spirally distributed, and its shape was negatively correlated with the nitrogen temperature. Thermodynamic effects reduced the vapor volume in the cavitation region and vorticity primarily at the leading edge, thus inhibiting the development of TLV. Enstrophy analysis was proposed to reveal the energy losses on TLV, and the enstrophy dissipation rate showed good predictability for TLV evolution. With the increasing temperature, the intensity of energy losses was reduced due to the thermal effects combined with weak cavitation intensity. Moreover, the change of temperature mainly influenced the primary tip leakage vortex (PTLV) but had minimal impact of the secondary tip leakage vortex. The energy losses were positive correlated with TLV, and PTLV was offset to the hub of the inducer due to the thermodynamic effects. Thus, the tip leakage can be considered as a key parameter to minimize the occurrence of thermodynamic cavitation in a liquid nitrogen inducer to provide a reference for the design of the inducer.